Structure evolution of tungsten coatings exposed to plasma flows under ITER ELM relevant conditions - Malykhin, S.V.; Surovitskiy, S.V.; Makhlaj, V.A.; Aksenov, N.N.; Byrka, O.V.; Borisova, S.S.; Herashchenko, S.S.; Reshetnyak, V.V. (Вопросы атомной науки и техники, 2017)
Structure, substructure and stress parameters both on the surface and distributed by depth in the tungsten/steel coatings exposed to high energy hydrogen plasma fluxes were studied by X-ray diffraction methods. The hydrogen plasma exposure results in the following recrystallization processes in the thin surface layer of the coating: appearing the texture axis [100] normal to the surface; increasing the coherence length from 60 nm in the initial state to 80 nm after the plasma exposure; completely annealed micro-strains; and dislocation density lowered twice in the exposed surface layer - all these facts confirm the thermal character of the hydrogen plasma influence. No structure variations were observed already at the depth near 1 m of the coating.